2021
DOI: 10.1007/s11301-021-00242-9
|View full text |Cite
|
Sign up to set email alerts
|

Million dollar personality: a systematic literature review on personality in crowdfunding

Abstract: Expressed personality traits can play a pivotal role in convincing investors in crowdfunding. Our study answers the research question: What is the current body of knowledge regarding the relationship between personality factors and crowdfunding success and where are knowledge gaps where the literature is silent? In our literature review, we therefore analyze and categorize (1) the results provided by quantitative studies on the relationship between the personality of entrepreneurs and crowdfunding success and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 126 publications
(198 reference statements)
0
11
0
Order By: Relevance
“…Considering a more subjective dimension concerning the implied signals involved in these factors, the entrepreneurial passion demonstrated by the founders, for instance, in their pitch videos or through the project description (Li et al, 2017), or even displays of narcissism , have been shown to motivate potential backers to support a project and increase crowdfunding performance. Moreover, a recent review on personality characteristics of project teams emphasizes the importance of personality traits for crowdfunding performance (Neuhaus et al, 2021), which might be perceived through the pitch video and the project description and taken into account by the crowd. These factors can thus constitute elements of different subsets of signals, as they can be employed through the pitch video, a basic quality indicator, or the project description, which can be assigned to signals referring to trust-building measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering a more subjective dimension concerning the implied signals involved in these factors, the entrepreneurial passion demonstrated by the founders, for instance, in their pitch videos or through the project description (Li et al, 2017), or even displays of narcissism , have been shown to motivate potential backers to support a project and increase crowdfunding performance. Moreover, a recent review on personality characteristics of project teams emphasizes the importance of personality traits for crowdfunding performance (Neuhaus et al, 2021), which might be perceived through the pitch video and the project description and taken into account by the crowd. These factors can thus constitute elements of different subsets of signals, as they can be employed through the pitch video, a basic quality indicator, or the project description, which can be assigned to signals referring to trust-building measures.…”
Section: Discussionmentioning
confidence: 99%
“…Appendix: Project success factors and suggested factors with a potential impact on project overfunding • Experience of project founders (crowdfunding or professional experience) • Internal social capital, positive psychological capital • Team composition (e.g., gender) • Personality characteristics Allison et al (2017), , Anglin, Wolfe, et al (2018), Davies and Giovannetti (2018), Neuhaus et al (2021), Ullah and Zhou (2020) Receiver (Crowd) Perspective Perception of project and of own contribution n.o.…”
Section: Limitations and Avenues For Future Researchmentioning
confidence: 99%
“…To the end of comprehensively covering the relevant literature, we searched within three electronic literature databases: EBSCO Host, Scopus, and Web of Science (Kuckertz and Block 2021 ; Wanyama et al 2021 ). These databases are considered the most important and widely used within research in business and the social sciences and consequently find frequent use for SLRs within the business field (examples are Eckert and Hüsig 2022 ; Lu et al 2018b ; Neuhaus et al 2021 ; Tueanrat et al 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Thus far, the role of backers’ personal characteristics has largely been ignored: A systematic review by Neuhaus et al (2022) identified no more than nine studies on the topic which, in addition, focus on very different characteristics. Given that we cannot deduce important antecedents from existing research, we focus on two personal characteristics presumably most closely related to motivations for crowdfunding: backers’ attitudes towards science and their experience with charitable giving and crowdfunding.…”
Section: Backers Of Science-related Crowdfunding Projectsmentioning
confidence: 99%